A Journey to Understand Glucose Homeostasis: Starting from Rat Glucose Transporter Type 2 Promoter Cloning to Hyperglycemia - Yong Ho Ahn (Diabetes & Metabolism Journal, 2018)
My professional journey to understand the glucose homeostasis began in the 1990s, starting from cloning of the promoter region of glucose transporter type 2 (GLUT2) gene that led us to establish research foundation of my group. When I was a graduate student, I simply thought that hyperglycemia, a typical clinical manifestation of type 2 diabetes mellitus (T2DM), could be caused by a defect in the glucose transport system in the body. Thus, if a molecular mechanism controlling glucose transport system could be understood, treatment of T2DM could be possible. In the early 70s, hyperglycemia was thought to develop primarily due to a defect in the muscle and adipose tissue; thus, muscle/adipose tissue type glucose transporter (GLUT4) became a major research interest in the diabetology. However, glucose utilization occurs not only in muscle/adipose tissue but also in liver and brain. Thus, I was interested in the hepatic glucose transport system, where glucose storage and release are the most actively occurring.